On the reflex mechanisms of cervical transcutaneous spinal cord stimulation in human subjects - Milosevic, Matija; Masugi, Yohei; Sasaki, Atsushi; Sayenko, Dimitry G.; Nakazawa, Kimitaka (Journal of neurophysiology, 2019)
Transcutaneous and epidural electrical spinal cord stimulation techniques are becoming more valuable as electrophysiological and clinical tools. Recently, remarkable recovery of the upper limb sensorimotor function during cervical spinal stimulation was demonstrated. In the present study, we sought to elucidate the neural mechanisms underlying the effects of transcutaneous spinal cord stimulation (tSCS) of the cervical spine. We hypothesized that cervical tSCS can be used to selectively activate the sensory route entering the spinal cord and transsynaptically converge on upper limb motor pools. To test this hypothesis, we applied cervical tSCS using paired stimuli (homosynaptic depression) and during passive muscle stretching of the wrist flexor (presynaptic inhibition via Ia afferents), voluntary hand muscle contraction (descending facilitation of motoneuron pool), and muscle-tendon vibration of the wrist (presynaptic inhibition via afferent occlusion). Our results demonstrate significant inhibition of the second evoked response during paired stimulus delivery, inhibition of responses during passive muscle stretching and muscle-tendon vibration, and facilitation during voluntary muscle contraction, which share similarities with responses evoked during lumbosacral tSCS. These results indicate that the route of the stimulation current transmission passes via afferents in the dorsal roots through the spinal cord to activate the motor pools and potentially interneuronal networks projecting to upper limb muscles. Using a novel stimulation paradigm, our study is the first to present evidence of the sensory neuronal pathway of the cervical tSCS propagation. Overall, our work demonstrates the utility and sensitivity of cervical tSCS to engage the sensory pathway projecting to the upper limbs. NEW & NOTEWORTHY Despite therapeutic effects that have been demonstrated previously using noninvasive cervical spinal stimulation, it has been unclear whether, and to what degree, the stimulation can activate the sensory afferent system. Our study presents evidence that cervical transcutaneous spinal cord stimulation can engage the sensory pathways and transsynaptically converge on motor pools projecting to upper limb muscles, demonstrating the utility and sensitivity of cervical spinal stimulation for electrophysiological assessments and neurorehabilitation.